The Influence of Music on Adolescent Psychology under Construction at Corpus Christi Lawang, Malang, East Java - Sabath, Brill Obed; Ardini, Ni Wayan (Journal of Aesthetics, Creativity and Art Management, 2024)
This research aims to determine the influence of music on the psychological aspects of teenagers involved in coaching at Corpus Christi Lawang in Malang District, East Java, Indonesia. The research method used is a qualitative approach using observation, interview, and literature study data collection techniques. The findings of this study highlight that music influences various psychological aspects of adolescents, including mood, behavior, self-identity, and social interactions. The results of this research provide an in-depth understanding of the role of music in the development of the young generation in Corpus Christi Lawang. The practical implications of this research can help foundation administrators design more effective coaching programs by utilizing music's power to influence adolescent psychology positively. Music's influence on adolescent psychology at Corpus Christi Lawang aims to influence a person's emotions and provide calm to the subconscious (id) which can be controlled and build emotional, spiritual, and social structures in the rhythm of music when listening and expressing it.